2015
DOI: 10.3390/ijms160921056
|View full text |Cite
|
Sign up to set email alerts
|

Weekly Treatment of 2-Hydroxypropyl-β-cyclodextrin Improves Intracellular Cholesterol Levels in LDL Receptor Knockout Mice

Abstract: Recently, the importance of lysosomes in the context of the metabolic syndrome has received increased attention. Increased lysosomal cholesterol storage and cholesterol crystallization inside macrophages have been linked to several metabolic diseases, such as atherosclerosis and non-alcoholic fatty liver disease (NAFLD). Two-hydroxypropyl-β-cyclodextrin (HP-B-CD) is able to redirect lysosomal cholesterol to the cytoplasm in Niemann-Pick type C1 disease, a lysosomal storage disorder. We hypothesize that HP-B-CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…The number of foam cells and foamy MØs were markedly decreased in the APOE-AAV group compared with that in the control group (Online Figure VIII B). 2-Hydroxypropyl-ß-cyclodextrin (CD) has been reported to induce the plaque regression by removing cholesterol crystals 3234 , lowering intracellular cholesterol levels in vivo 35 , and inducing MØ reprogramming and liver X receptor (LXR)-dependent atheroprotection 36 . Ldlr −/− mice with advanced atherosclerosis (WD for 25 weeks) were injected with CD (2 g/kg body weight) or PBS (vehicle control) for 8 weeks on a WD.…”
Section: Resultsmentioning
confidence: 99%
“…The number of foam cells and foamy MØs were markedly decreased in the APOE-AAV group compared with that in the control group (Online Figure VIII B). 2-Hydroxypropyl-ß-cyclodextrin (CD) has been reported to induce the plaque regression by removing cholesterol crystals 3234 , lowering intracellular cholesterol levels in vivo 35 , and inducing MØ reprogramming and liver X receptor (LXR)-dependent atheroprotection 36 . Ldlr −/− mice with advanced atherosclerosis (WD for 25 weeks) were injected with CD (2 g/kg body weight) or PBS (vehicle control) for 8 weeks on a WD.…”
Section: Resultsmentioning
confidence: 99%
“…The central role of KCs in the pathogenesis of NAFLD has been suggested by several studies in mouse models where the ablation of KCs determined the marked reduction of hepatic insulin resistance and inflammation in diet-induced steatosis [109, 110]. In experimental NASH, macrophages are characterized by the accumulation of large amounts of toxic lipids [99, 111] and cholesterol crystals [112]; fat-laden KCs exhibit a switch to a proinflammatory (M1) phenotype, which is reversible by inhibition of lipogenesis [99, 113]. Moreover, data obtained by different research groups showed that chemical depletion of KCs was able to prevent the release of proinflammatory cytokines and to alleviate liver damage [114].…”
Section: Liver Tissue Inflammationmentioning
confidence: 99%
“…In this way, atherosclerosis, obesity, and hepatosteatosis may all represent acquired lysosomal storage disorders [ 49 ]. Compounds that promote the mobilization of cholesterol crystals from the lysosome and into the cytoplasm (e.g., β -cyclodextrins) have been promoted as potential therapeutic compounds for these disorders [ 50 52 ]. This is in contrast to oleate and other unsaturated fatty acids that stimulate, but do not stall, flow through the autophagy pathway [ 34 ].…”
Section: Introductionmentioning
confidence: 99%